Implementasi Business Model Canvas dalam Penguatan Perencanaan Usaha TKML di Kabupaten Kubu Raya - Irba Muhlas Sambodo; Singgih Tiwut Atmojo; Aditya Nugraha; Trisna Al Hadji AT; Wahyu Setiyadi (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2026)
This community service activity aimed to strengthen business planning capacity among Tenaga Kerja Mandiri Lanjutan (TKML) in Kubu Raya Regency, West Kalimantan, where participants commonly face limitations in structured business planning that affect business sustainability. The activity applied a participatory mentoring approach through training, field visits, group discussions, and direct assistance tailored to the characteristics of each business. The program involved nine TKML groups designated by the Ministry of Manpower of the Republic of Indonesia. The results indicate that participants gained a clearer understanding of key business components, value creation processes, and internal strengths and weaknesses. The use of the Business Model Canvas supported participants in organizing business ideas, enhancing strategic thinking, and developing more structured and sustainable business plans. In addition, this activity reinforced the role of higher education institutions in supporting government initiatives on employment expansion through community service. Overall, the findings demonstrate that mentoring-based business planning is effective in improving TKML capacity and has the potential to be replicated in other regions to support independent workforce empowerment and job creation.